23rd Pauline Cerasoli Lecture Educating for Professionalism: The Science of Caring. The Art of Healing. Issue 4 (2nd December 2021) - Swisher, Laura Lee
Abstract: Although the physical therapy profession has worked tirelessly toward recognition as a true profession, we know little about best practices in educating for and evaluating professionalism. These complex and uncertain times challenge traditional notions, calling for nuanced multidimensional understandings of both collective and individual professionalism. A review of the current state of professionalism education in physical therapy, limitations of traditional reductionist notions of professionalism, and research in professionalism provides a framework for considering a multidimensional model of professionalism. By proposing a model that reconciles undermining dichotomies (such as evidence/value, individual/social, science/art, and clinical/professional), we can advance the development of alternative models of teaching professionalism. The professionalism curriculum of the future must be grounded in sound theory, a broad range of foundational and behavioral sciences, ongoing research, social values of justice and equity, a strong professional identity, and faculty committed to advancing the science and art of professionalism. It is an honor to have been selected to give the Pauline Cerasoli lecture because Polly Cerasoli was an extraordinary educator and person. I had the opportunity to meet Polly on several occasions, and others have described her professionalism as a teacher, administrator, and accreditation Team Leader. Polly lived out the meaning of professionalism and moral courage. I am grateful to the Cerasoli family for establishing this lectureship and to the Academy of Physical Therapy Educators for selecting me to present during this event named in her honor. Of course, I wish that we could be together for this event to share the rich interaction that comes with being together. However, we are fortunate be able to connect virtually. I am grateful to Texas Woman's University in Dallas and especially Dr. Ann Medley (Program Director) who was kind enough to provide the setting and technology support for this lecture. When I learned in 2019 that I had been selected for the honor of being the Polly Cerasoli lecturer, few people knew what 2020 would bring. What a year it was! Having come through the uncertain days of 2020, I have no doubt that ethics and professionalism are more important than ever.